การพัฒนาแบบตรวจสอบกระบวนการประเมินผู้เรียนระดับประถมศึกษาด้วยแฟ้มสะสมงาน กลุ่มสาระการเรียนรู้ภาษาไทย - อรรถพล ศรีไพจิตรวรกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The purposes of this research were (1) to synthesize the main steps of elementary students’ portfolio assessment process in Thai language subject area, (2) to develop the elementary students’ portfolio assessment process checklist for Thai language subject area, and (3) to validate elementary students’ portfolio assessment process checklist for Thai language subject area. Data were collected by using a study of related literatures, an interview of 4 teachers, and 5 experts as well as an observation of Thai language teachers in implementing students’ portfolio assessment process in 2 schools. Analytical induction was employed to analyze the data. Research instruments were research and document analysis forms, observation form, and interview form. The research findings were as follows: 1. The main steps of elementary students’ portfolio assessment process in the Thai language subject area compised of 5 steps, i.e., (1) planning the portfolio, (2) conllecting products, (3) self assessment and evaluation, (4) revising products, and (5) connection. 2. The elementary students’ portfolio assessment process checklist for thai language subject area Included 5 steps. Each step consisted of 13 checkpoints and each checkponit consisted of 4 to 5 checklist items. There were totally 58 checklist items in the developed checklist. 3. The results of validation of the developed elementary students’ portfolio assessment process checklist for Thai language subject area were (1) Cronbach s alpha coefficient of each step and overall were in the high levels, and (2) The users’ is opnion on the elementary students’ portfolio assessment process checklist for Thai language subject area was high in every standard, i.e., utility, feasibility, accuracy, and propriety standard.